Histamine as a marker for hydroxyl radicals - T.-L. Ching; R. M. van der Hee; N. M. Bhoelan; J. Blauw; W. M. P. B. Menge; J. de Jong; A. Bast (Mediators of Inflammation)
During inflammation an influx of neutrophils and release of mediators from mast cells (such as histamine) take place. The stimulated neutrophils can produce reactive oxygen species (ROS). One of these ROS is the highly reactive hydroxyl radical (OH.). It would be interesting to be able to quantify the extent of ROS formation. We investigated if histamine which is present at the inflammation site can serve as an endogenous marker for the formation of OH.. We found that histamine after incubation with OH. gave two distinct products in our HPLC system. One of the products gave the same characteristics as the synthesized 2-imidazolone derivative of histamine. This suggests that this derivative will be formed when histamine is incubated with OH..